Alimentary Tract Manifestations of Bovine Adenovirus Infections - Thompson, K. G. (1981)
Two calves and a feedlot steer with systemic bovine adenovirus infection had hemorrhagic and necrotizing lesions confined to the digestive tract. In one calf there was severe, multifocal, necrotizing, hemorrhagic rumenitis, omasitis, abomasitis, enteritis and colitis. Small intestinal lesions were predominantly in Peyer's patches. Multifocal necrotizing abomasitis was the principal change in the other calf. Large amphophilic intranuclear inclusions typical of bovine adenovirus were common in swollen vascular endothelial cells. Bovine adenovirus was isolated from the former calf. The steer had diffuse hemorrhagic enterocolitis and large numbers of BAV inclusions in vascular endothelial cells of the intestinal lamina propria. Serum-neutralization tests to bovine adenovirus type 3 on acute and convalescent samples from six clinically affected in—contact animals revealed fourfold elevations in two.